Unveiling Peru’s Agricultural Diversity: Navigating Historical and Future Trends in a Post-COVID-19 Context - Chavez, Segundo G. (2024)
Over a comprehensive 5-year assessment, and extrapolating it prospectively until 2025, a thorough examination was conducted of productive agrobiodiversity in nine rural agricultural districts across Peru. The present study involved in-depth interviews with 180 representative farmers of the Coast, Highlands, and Jungle natural regions. Employing the Shannon–Weiner diversity index and the Margalef species richness index, the dynamics within years and across different zones were analyzed. Utilizing quadratic trend models, we assessed the frequency of each crop, aiming for the optimal fit concerning absolute deviation from the mean, mean squared deviation, and mean absolute percentage error. These findings revealed five distinct crop types—tuberous, fruits, cereals, legumes, and roots—distributed across 25 diverse families. Looking ahead to 2025, our projections indicated positive trends in 15 families and negative trends in 9 crop families. The nuanced mathematical distinctions observed in crop management decisions varied significantly depending on the specific area and year, underscoring the importance of localized considerations in agricultural planning.